Arterial stiffness assessment in patients with phenylketonuria. Issue 51 (December 2017) - Hermida-Ameijeiras, Alvaro; Crujeiras, Vanesa; Roca, Iria; Calvo, Carlos; Leis, Rosaura; Couce, María-Luz
Abstract : Abstract: In patients with phenylketonuria (PKU) compliant to diet greater tendency to overweight and higher inflammatory biomarkers levels than controls were reported. Although this could lead to atherogenesis, the elastic properties of large arteries in PKU patients have never been assessed. The aim of this study was to assess arterial stiffness measured by applanation tonometry in PKU patients compared to healthy controls. We carried out a cross-sectional study in 41 PKU patients (range age: 6–50 years old) and 41 age- and gender-matched healthy controls. Evaluated data included pharmacological treatment with sapropterin, clinical, and biochemical parameters. Aortic stiffness was assessed noninvasively by applanation tonometry measuring central blood pressure, aortic augmentation index (Aix@HR75), augmentation pressure (AP), and pulse wave velocity (PWV). We found higher PWV in classic PKU patients (6.60 m/second vs 5.26 m/second; P: .044). Percentage of PKU patients with PWV above 90 percentile was higher than controls (14.63% vs 2.32%; P : .048). A positive relationship was observed between the annual Phe median and PWV (r: 0.496; P : .012). PKU subjects with lower Phe tolerance showed more body weight (67.6 kg vs 56.8 kg; P : .012) and more PWV than those with higher Phe tolerance (6.55 m/second vs 5.42 m/second; P : .044). Our data show increased aortic stiffness in PKU patients, measured by applanation tonometry, when compared to healthy controls. Higher Phe levels are associated with a bigger PWV increase, which is not present in those subjects compliant to diet or under sapropterin treatment. These results could have marked effects in both research and clinical daily practice for a proper evaluation of cardiovascular risk in PKU subjects. Abstract : Supplemental Digital Content is available in the text